Aerococcus: an increasingly acknowledged human pathogen. (January 2016) - Rasmussen, M.
Abstract: Aerococci have often been misidentified as streptococci in microbiology laboratories, leading to an underestimation of these bacteria as causes of human infections. An increased awareness of aerococci and the introduction of matrix-assisted laser desorption ionization time-of-flight mass spectrometry, has led to an increased isolation of Aerococcus urinae and Aerococcus sanguinicola from human urine and blood. The two species are found in human urine and can cause urinary tract infections (UTI). Aerococcus urinae can, in older males with underlying urinary tract conditions, cause invasive infections such as urosepsis or infective endocarditis. The prognosis of invasive aerococcal infections appears to be relatively favourable despite the old age of patients and their many comorbidities. Though clinical breakpoints are still not in place, aerococci seem to be sensitive to penicillins, carbapenems and vancomycin. There is synergy between penicillin and aminoglycosides against some A. urinae isolates and this combination is often used in aerococcal infective endocarditis. The treatment of complicated aerococcal UTI is not obvious as many isolates are resistant to fluoroquinolones. In addition, A. urinae is resistant to sulphamethoxazole, and there are methodological problems in the determination of trimethoprim sensitivity. In complicated UTI, ampicillin is probably a safe treatment option, whereas nitrofurantoin is probably effective in uncomplicated UTI. Treatment studies in aerococcal infections are needed as is a better understanding of the natural niches for aerococci and the pathogenesis and clinical course of aerococcal infections.